Longer dialysis session length is associated with better intermediate outcomes and survival among patients on in-center three times per week hemodialysis: results from the Dialysis Outcomes and Practice Patterns Study (DOPPS) - Tentori, Francesca; Bommer, Jürgen (Nephrology, dialysis, transplantation, 2012)
The paper by Tentori at al confirms previous findings about the positive impact of treatment time on outcome […], taking into account that urea kinetics is not